LIMPASAN PERMUKAAN DAN EROSI TANAH SETELAH SEPULUH TAHUN MENGGUNAKAN SISTEM TANAMAN LORONG - Titiek Islami; W.H. Utomo (Universitas Tribhuwana Tunggadewi, 2006)
Field experiments had been carried out to study the effect of 10 years alley cropping system on surface run off and soil erosion. Experiments were carried out on Alfisols at Jatikerto, Malang and on Vertisols at Ngrimbi, Jombang, East Java. The results showed that after 10 years planting tree crops and or grass as hedgerow in between food crops very efeective to decrease surface run off and soil erosion. After 10 years of planting the tree crops, the alley cropping system could decrease surface run off and soil erosion more than 40% (compared to that of the non alley cropping system) At the same time, soil erosion decrease up to 60% of the non alley treatment. The use grass as hedgerow crops yielded a better result, in term of surface run off and soil erosion. A comparison between tree species, Flemingia and Gliricidia are better than Leucaena